353 B-BLOCKERS EFFECTS ACCORDING TO SEX: DO SELECTIVITY AND DOSE EQUALLY MATTER?. (15th December 2022) - Salvioni, Elisabetta; Paolillo, Stfania; Galotta, Arianna; Mapelli, Massimo; Mattavelli, Irene; Basile, Christian; Vignati, Carlo; Moscucci, Federica; Piepoli, Massimo; Agostoni, Piergiuseppe
Abstract: Background: β-blockers are one of the four recommended disease-modifying classes of drugs for the treatment of heart failure with reduced ejection fraction (HFrEF). Although their efficacy and prognostic role is unquestionable in the general population of HFrEF patients, the differences in their effect in relation to sex have not been yet investigated in detail. The present study analyzed a large, real-world, Italian population of HFrEF patients aiming to highlight any prognostic difference between males and females in relation to dose and β-selectivity of the ongoing β-blocker treatment. Methods: Out of the 7900 HFrEF patients included in the MECKI score registry, we retrospectively analyzed those treated with β-blockers. We investigated the prognostic role of β-selectivity, dividing the population in assuming β1/β2-receptor blockers (carvedilol) vs. β1-selective blockers (bisoprolol, nebivolol or metoprolol), according to sex, and the prognostic role of daily carvedilol-equivalent β-blocker dose in relation to sex. The primary outcome of the study was the composite of all cause mortality, urgent heart transplant and LVAD implant analyzed at 5 years, both as raw data and after correction of potential confounders. Results: 6784 HFrEF patients treated with β-blockers were analyzed (1215 females, 5569 males). Patients median follow-up was 4.05 years [1.72-7.47]: 4.37 [1.6-8.13] for females and 3.99 [1.75-7.3] for males (p=ns). According to β-selectivity no prognostic differences were found in the general population, as in female or males (Fig. 1 right panel). Stratification of patients according to β-blockers equivalent dose showed significant difference among groups: mortality decreases with increasing β-blockers dose in both males and females (Fig. 1, left panel), both at baseline and after adjustment for the main confounders (LVEF, age, peakVO2, systolic pressure, hemoglobin, rest heart rate; VE/VCO2 slope, etiology. ICD, MDRD). Conclusions: In a large, real-life population of chronic HFrEF patients analyzed according to sex, no prognostic differences were found between stratifying for β-selectivity. A better outcome was observed in subjects receiving a high daily dose, independently from sex.